ANALISIS DAMPAK PEMBANGUNAN PERUMAHAN TERHADAP KONDISI SOSIAL EKONOMI MASYARAKAT DI KOTA KANDANGAN KABUPATEN HULU SUNGAI SELATAN - HENDRA ADITYA WARDHANA; KHAIRI PAHLEVI (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
The purpose of the research is to see how the impact of housing development on the socio-economic conditions of people in Kandangan town, Hulu Sungai Selatan regency.Data were collected by using questionnaire method on 91 respondents by using purposive sampling method.               Result of research based on social condition of society indicate Social relation between residents around residential area remain harmonious, new class emergence that resident of residence does not cause jealousy from local citizen, local citizen feel that resident of housing also part of society exist because they willing to follow norm together. While the impact on the community economy indicates the influence of housing development on the livelihood of the citizens is significant, many residents who changed the profession to be workers in housing, such as a night watchman, a small trader, a housekeeper or a security guard. residents also feel that finding a work field becomes easier after housing. The cost of living tends to be the same without increasing.Keywords : impact of socio-economic condition of people, impact of housing developement